Investigation on Dynamic Resource Allocation for Multiple Antenna OFDM Based System - P. Chiranjeevi; N. Bhargavi (New Approaches in Engineering Research Vol. 12, 2021)
We propose a transceiver structure that reduces interference between transmitting and receiving subcarriers in this study. Its performance in terms of signal to interference and noise ratio (SINR) is assessed using both analysis and simulation, and it is then incorporated into a recently proposed cooperation strategy for Orthogonal Frequency Division Multiple Access (OFDMA) systems to test its performance under realistic conditions. In multipath channels with non-sample-spaced time delays, the conventional Discrete Fourier Transform (DFT)-based technique will induce energy leakage. The improved DFT-based channel estimation approach extends the LS estimate in frequency domain using the symmetric property, calculates the changing rate of the leakage energy, and identifies viable pathways based on the changing rate. It is noticed that the multicast scheme with the proposed method can achieve higher capacity than the uni-cast scheme or the mixed cases. The more multicast users exit, the higher system capacities can be achieved.